Chapter Life Cycle Assessment as a Tool to Implement Sustainable Development in the Bioeconomy and Circular Economy - Wrzosek, Justyna (InTechOpen, 2019)
In this chapter, the life cycle assessment was presented as a tool to implement sustainable development in the bioeconomy and circular economy. Bulky waste includes large items such as furniture, doors, flooring and mattresses. The management of bulky waste is a serious problem for European countries. The URBANREC project proposed a solution to this problem through the use of new technologies for the bulky waste processing. The aim of the URBANREC project is to implement an eco-innovative, integrated system of bulky waste management and demonstrate its effectiveness in various regions of Europe. The project has received funding from the European Union. In this chapter, the LCA environmental analysis was performed for the technology of grinding bulky waste using a water jet by the Ecofrag company. The calculations were carried out using SimaPro 8.5.2.0. The LCA analysis shows that the reuse of foams and mattresses contributes to the avoidance of their targeted production, which is related with the reduction of greenhouse gas emission and consumption of fossil raw materials.